PENGOLAHAN LINDI (LEACHEATE) DENGAN METODE MOVING BED BIOFILM REACTOR (MBBR) DENGAN PROSES AEROBIK-ANOKSIK UNTUK MENURUNKAN KONSENTRASI COD, TSS, DAN AMONIA. - Anisa Nurrahma; Firra Rosariawari (EnviroUS, 2021)
ABSTRACT Leachate contains high levels of organic matter, TSS and ammonia. Moving Bed Biofilm Reactor (MBBR) is a biological treatment that can reduce the concentration contained in leachate. The purpose of this study was to determine the ability of MBBR to reduce the content of organic matter, TSS, and ammonia, by using variations in the detention time of aerobic-anoxic processes and sticky media. This research is a laboratory scale research. Leachate samples came from the Kotawaringin Timur TPA Inlet. The reactor is operated in batches. During the aerobic process the moving media is assisted by an aerator pump and submersible pump, while in the anoxic process it is only from a submersible pump. The MBBR processing used has a capacity of 5L with a media capacity of 2L. The variations of the media used were K1 and K3 caldness, while the aerobic detention time was 14.5 hours - anoxic 10 hours and aerobic 10 hours anoxic 7 hours. The results obtained show that MBBR can be used to treat leachate. The best decrease in COD, TSS, and ammonia concentrations occurred in K1 media with 14.5-anoxic 10-hour aerobic detention time with a reduction of 74.8%, 93.14%, and 83.72%.